Does general experience affect self‐assessment?. (22nd May 2018) - Rezaiefar, Parisa; Forse, Kelly; Burns, Joseph K; Johnston, Sharon; Muggah, Elizabeth; Kendall, Claire; Archibald, Douglas
Summary: Background: The assessment of clinical competence is critical in medical education. Understanding the effect of general experience on a physician's self‐assessment would help design more effective curricula and evaluations of procedural skills in postgraduate training and continuing professional development (CPD). In this observational study, we assessed the effect of general experience on the correlation between confidence and competence amongst experienced clinicians (ECs) and postgraduate trainees (PGTs) when learning an office‐based procedure in pessary care. Methods: We recruited 19 first‐year family medicine residents and 18 family medicine faculty members in two outpatient academic clinics. All participants attended a simulation‐based workshop for a routine gynaecological office procedure. We used a confidence survey as a measure of the participants' self‐assessed competence and an objective structured clinical examination (OSCE) to evaluate participants' competence before and after the workshop. The assessment of clinical competence is critical in medical education Results: We found no significant correlation between confidence and competence at baseline for either group (EC, r  = 0.25, p = 0.35; PGT, r  = 0.15, p = 0.60). After the workshop, we observed a statistically significant correlation between confidence and competence for ECs ( r  = 0.60, p = 0.01), but not for PGTs. The change in this correlation was not statistically significant for either group, however. Discussion: Our findings suggest that ECs are not any more accurate in the assessment of their competence compared with PGTs. All procedural skills curricula can benefit from OSCE‐format evaluation to better evaluate the improvement in performance of participants.